Sodium acetate regulates milk fat synthesis through the activation of GPR41/GPR43 signaling pathway - Qi, Yingao; Zheng, Tenghui; Liu, Xinghong; Yang, Siwang; Li, Qihui; Shao, Jiayuan; Zeng, Xiangfang; Guan, Wutai; Zhang, Shihai (Frontiers in Nutrition, 2023)
Background: Fat is a critical component in milk, which provided energy for the early growth and development of mammals. Milk fat is positively related to the concentration of acetate in the blood, while the underlying mechanism is still unclear. Objective: This study is to investigate the effects of sodium acetate (NaAc) on milk fat synthesis in the mammary gland, and explored the underlying mechanism. Methods: In vitro experiments were carried out in mouse mammary epithelial cell line (HC11) cells cultured with NaAc to explore the potential pathway of NaAc on milk fat synthesis. Furthermore, 24 pregnant mice (from d 18.5 of gestation to d 7 of lactation, exposed to 200 mM NaAc drinking water) were used as an in vivo model to verify the results. Results: In this study, we found that NaAc promoted milk fat synthesis and the expression of related genes and proteins in HC11 mammary epithelial cells with the activation of GPCR and mTORC1 signaling pathways (P < 0.05). Pretreatment with the mTORC1 inhibitors and G protein inhibitors attenuated the NaAc-induced milk fat synthesis in HC11 mammary epithelial cells (P < 0.05). Importantly, the effect of NaAc on milk synthesis was attenuated in GPR41 and GPR43 knockdown HC11 mammary epithelial cells (P < 0.05). This evidence indicates that NaAc might regulate milk fat synthesis through the GPR41/GPR43-mTORC1 pathway. Consistently, in in vivo experiment, dietary supplementation with NaAc significantly increased milk fat content and fat synthesis-related proteins in mice mammary glands with the activation of mTORC1 and GPCR signaling pathways at peak lactation (P < 0.05). Conclusion: The addition of NaAc promoted the increase of milk fat synthesis in HC11 mammary epithelial cells and mice mammary glands at peak lactation. Mechanistically, NaAc activates GPR41 and GPR43 receptors, leading to the activation of the mTORC1 signaling pathway to promote the synthesis of milk fat.